Marketing of Coffee is in a Difficult Path-an Analysis under Global Environment - Murugan, S. (Indian Journal of Marketing, 2005)
Coffee is one of the most important beverages, which is non-alcoholic like tea, cocoa etc. It has been said that it comes next to oil in political and economic importance. A large number of countries in Latin America, Africa and elsewhere rely heavily on coffee exports for their income, and this has made coffee important in politics. It is one of the important commercial crops grown in tropical regions. Coffee possesses a unique and characteristic aroma and is consumed throughout the world. It is one of the major traded commodities in the international market with an annual turnover of more than 10 billion dollars.